ASSOCIATION OF VIRULENCE FACTOR (PANTONâ€“VALENTINE LEUKOCIDIN) WITH MECA GENE IN STAPHYLOCOCCUS AUREUS ISOLATES IN TERTIARY CARE HOSPITAL - Patil, Nilima R; Mv, Ghorpade (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objectives: This study was aimed to determine the association between mecA gene and virulence genes such as pvl gene in strains of S. aureus and to determine the prevalence of the pvl gene in S. aureus isolates using the polymerase chain reaction (PCR) technique. Methods: A total of 200 non-repeated, confirmed clinical isolates of S. aureus were used from various departments. Cefoxitin (30 ug) disc diffusion method was used as phenotypic method for detection of methicillin-resistant S. aureus (MRSA). We used PCR amplification to test for the pvl and mecA gene in S. aureus isolates. Results: Of 200 strains of S. aureus isolated in our hospital, 60 (30%) were identified as MRSA based on cefoxitin disc diffusion method. These same 30 isolates were confirmed for mecA gene by PCR. All strains had mecA gene. All mecA positive strains of S. aureus were tested for pvl gene. Of 200 S. aureus, 123 (61.5%) strains were pvl positive. Among which 33 (55%) were pvl positive MRSA and 90 (64.28%) pvl positive methicillin-susceptible S. aureus (MSSA) strains. Conclusion: The prevalence of the pvl among the MRSA isolates was found relatively higher in number among pus samples which indicate a possible key role of pvl in pathogenesis of pyogenic infections, especially skin and soft tissue infections in community setting.